Weeping in Modern Jihadi Groups. (14th September 2020) - Hegghammer, Thomas
Abstract: Abstract This article, using a wide range of primary sources, describes the practice of weeping ( bukā ) in contemporary jihadi groups. It shows that weeping is widespread and encouraged in militant Islamist groups such as al-Qaida and Islamic State. Modern jihadis weep in at least six main types of situations: during prayer, during sermons, when listening to hymns, pre- and post-combat, on losing comrades, and upon seeing civilian Muslim suffering. Weeping is socially appreciated; it often happens in groups, it is rewarded with praise and honorifics, and it is advertised in propaganda. Weeping for more mundane reasons is also reported, but not similarly valued. The findings add to other recent evidence suggesting modern jihadis are influenced by Sufism. Today's weeping practices also suggest a long historical association in Islam between asceticism and military jihad going back to eighth-century warrior-ascetics such as Ibn al-Mubārak (d. 797 Ce ).